Study on Hydrogen Transport into Ni, W, Cu and STS Metal Membranes using Current Transient Technique - Yun, Myung-Hee; Yeon, Jei-Won; Ahn, Hong-Joo; Song, Kyuseok (Asian Journal of Chemistry, 2012)
Hydrogen transport behaviours through the metals such as nickel, tungsten, copper and stainless steel have been investigated using the electrochemical hydrogen permeation method. The results show that hydrogen permeation current through the nickel increased as the charging potential increased. Hydrogen diffusion coefficient of metals was calculated from the hydrogen permeation transient profile. From the experimental results, it was realized that the flux of hydrogen permeating the metal depends on the metal composition and on the applied charging potential.